Reframing Student Participation in Ordinary Level Mathematics as an Equity Issue in Under-Resourced Rural Zimbabwean Schools - Claretah Makuvire; Pinias Chikuvadze (Journal of Educational Research and Practice, 2026)
Student participation in mathematics is increasingly recognised as an equity issue, particularly in under-resourced rural schools, where limited resources, examination pressure, teacher workload, and socio-cultural expectations may restrict learners’ opportunities to engage meaningfully with mathematical ideas. Although studies have examined mathematics anxiety, learner attitudes, teacher-centred instruction, and resource constraints, less attention has been given to how these factors interact to shape everyday participation in Ordinary Level Mathematics in rural Zimbabwe. This study examined the factors constraining and supporting students’ participation in five under-resourced rural secondary schools in the Lusulu Cluster of Binga District, Zimbabwe. An explanatory sequential mixed-methods case study design was used, involving questionnaires with 150 students and six Mathematics teachers, followed by focus group discussions, semi-structured interviews with heads of Mathematics departments and school heads, classroom observations, and document analysis. The findings show that participation was constrained by negative attitudes, low confidence, fear of failure, mathematics anxiety, gendered expectations, teacher-centred instruction, examination pressure, limited resources, and workload-related constraints. Structured questioning, peer-supported group work, hands-on activities, supportive teacher feedback, and school-family communication were perceived as promising strategies for supporting participation. This study reframes mathematics participation as a socially mediated and institutionally conditioned equity issue rather than a narrow matter of learner motivation. This study contributes to equity-oriented mathematics education by showing that meaningful participation in rural classrooms requires relationally safe, culturally responsive, resource-sensitive, and community-supported pedagogical conditions.